RANCANG BANGUN SISTEM LAYANAN KONSULTASI BANTUAN HUKUM PADA BAGIAN HUKUM SEKRETARIAT DAERAH KABUPATEN INDRAGIRI HILIR BERBASIS WEB - Bayu Rianto; Fitri Yunita; Riska Sari; Abdul Muni (JURNAL PERANGKAT LUNAK, 2022)
Until now, the Legal Division of the Regional Secretariat, specifically the Legal Aid Sub-Section, the Legal Division of the Regional Secretariat of Indragiri Hilir Regency, does not yet have a special system that assists the Legal Aid Sub-Division in providing Legal Aid Consultation services to Regional/Village Apparatus. In addition, there are several reasons that cause the Legal Aid Sub-Section to want a Web-based Legal Aid Consultation Service System. These reasons include: the implementation of direct consultation by coming to the office of the Legal Division of the Regional Secretariat, especially in the Legal Aid Sub-Section, it is deemed less effective for Regional/Village Apparatuses who are constrained by distance and time, and the difficulty of finding a consultation data recap due to the absence of a consultation data recap. Regional/Village Apparatus. To overcome these problems, a software development process is needed in the form of a Legal Aid Consultation Service System. The processes carried out are literature study, identification of needs, design or design, implementation or coding, testing or testing. The system development method used is the Waterfall method, while the analytical method used is the PIECES method which can be a reference in building a Legal Aid Consultation Service System at the Legal Section of the Regional Secretariat of Indragiri Hilir Regency. The modeling system used is a web-based UML (Unified Modeling Language) modeling language with PHP (Hypertext Preprocessor) programming language and Mysql database. As for software testing using blackbox testing, white box testing and questionnaire testing. With the Legal Aid Consultation Service System, it will be able to assist and facilitate Regional/Village Apparatuses in Indragiri Hilir Regency to carry out the Legal Consultation process through the System as well as for the Legal Aid Sub Division at the Legal Section of the Regional Secretariat of Indragiri Hilir Regency, it will be easy to search for consultation data recaps. carried out by the Regional/Village Apparatus in Indragiri Hilir Regency.